NCWCD efforts toward improving on-farm water management - Crookston, Mark A., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2005)
The Northern Colorado Water Conservancy District (NCWCD) formally established an IMS (Irrigation Management Service) in 1981 to promote improved on-farm water management. Programs include: 1) Weather Station Network, 2) Field-by-Field Irrigation Scheduling Demonstrations, 3) Surge Valve Loan Program, 4) Agricultural Best Management Practices Field Demonstrations, 5) Cooperative Salinity Program, and 6) Farm Turnout Low-Cost Gate Automation. Water measurement is a key to improved irrigation management. Needed measurements include flow deliveries to the field, crop water use (calculated from weather station data), local rainfall, tail water runoff, etc. Such measurements allow calculation of on-farm irrigation efficiency. This is a major step beyond just scheduling irrigations. It enables estimation of the volume of water used beneficially. Increased on-farm irrigation efficiency often requires improved flexibility in water deliveries from the canal to the farm turnout or field. However, this improved delivery flexibility can result in increased spills or waste in canal operations. An appropriate balance must be achieved. The IMS programs of NCWCD have experienced considerable success. However, institutional and economic barriers continue to inhibit needed improvements in some areas.
Improving on-farm water management
Not digitized by CSUL Digital Services.
Presented during the Third international conference on irrigation and drainage held March 30 - April 2, 2005 in San Diego, California. The theme of the conference was "Water district management and governance."